Penerapan Metode Bermain Peran sebagai Upaya untuk Meningkatkan Perkembangan Sosial Emosional Peserta Didik - Hikmawati Hikmawati; Takasun Takasun; Luk Luk Ul Hikmah (Unram Journal of Community Service, 2021)
The purpose of this community service activity is to apply the role-playing method as an effort to improve the socio-emotional development of students. The activity was held on November 17, 2021 at Mustika Rini Karangnongko Kindergarten with a total of 8 participants. The activity method consists of 3 stages, namely preparation, implementation, and reflection. The results of the activities for each stage are: in the preparation stage, the team prepares tools and materials, and guides students to carry out various activities so that they are ready to play roles. At the implementation stage, the team guides students to do three types of activities. Activity 1: Make a chicken-shaped mosaic from egg shells. Activity 2: Cracking eggs and frying eggs into egg rolls. Activity 3: Role-play being a seller and buyer of egg rolls. At the reflection stage, a recall and follow-up plan are carried out. Aspects that are assessed for the social emotional development of students in this role-playing activity are courage, self-confidence, independence, and communication. The socio-emotional development of students, namely students who are able to play the role of being a seller and a buyer, has developed according to expectations (BSH).